97 Decreasing invasive urinary tract infection screening in a paediatric emergency department: A quality improvement initiative. (29th October 2021) - Paluck, Felicia; Kestenbom, Inbal; Test, Gidon; Ostrow, Olivia; Brimmer, Brooke
Abstract: Primary Subject area: Emergency Medicine - Paediatric Background: Fever is a common presentation among children coming to the Emergency Department (ED) and a urinary tract infection (UTI) often needs to be excluded. Sterile techniques, like catheterization, are invasive, can be traumatizing to children, and are time consuming to complete. A two-step approach has been shown to reduce the catheterization rate in febrile, young children without unintended consequences. Objectives: Our aim was to implement a two-step approach for UTI screening in febrile children 6-24 months in order to decrease unnecessary urine catheterizations by 50% without impacting ED length of stay (LOS) or return visits (RVs). Design/Methods: After engaging key stakeholders and a nursing champion, we created a process map to understand the current urine collection process in our ED, and areas for targeted improvement. Using the model for improvement, we adopted a 2-step pathway for a suspected UTI in children 6-24 months as our change idea. The pathway involved identifying children who met inclusion criteria for UTI screening, followed by urine bag application and urinalysis (UA) if clinically indicated. Only if the UA was positive, a second urine sample was collected via catheterization, for repeat UA and culture. Through multiple PDSA cycles, our pathway was implemented in the ED along with concurrent staff education. The outcome measure was the rate of ED urine catheterizations. Process measures included the total number of urine cultures sent to microbiology and percent positivity. The balancing measures included ED LOS and RVs. Results: Since project initiation in July 2019, the ED catheterization rate decreased from 73% to 53% (Figure 1) and the number of urine cultures sent to Microbiology decreased by 23%. The number of urine cultures sent to Microbiology decreased by 23% with a mild improvement in the positivity rate by 2% (Figure 2). There was no significant change in RVs. There was a slight 10-min increase in ED LOS, most likely confounded by the COVID pandemic. Conclusion: Using improvement methodology, we successfully decreased the number of unnecessary catheterizations in children and the number of urine cultures sent to microbiology. Further refinements to our intervention are ongoing and include optimizing urine screening equipment in patient rooms, poster reminders, re-education for providers, and introducing a parent resource explaining the 2-step pathway. This improvement work is also being spread to the paediatric wards and can easily be adopted by other paediatric centres. It has also been adapted by the Choosing Wisely hospital campaign.